PERAN MAINTENANCE DALAM MEMODERASI PENGARUH TQM TERHADAP KINERJA PERUSAHAAN BOUNTY CRUISES DI PELABUHAN BENOA - Dewi, Ni Putu Tara Damayanti; Purnawati, Ni Ketut (E-Jurnal Manajemen; Vol 10 No 2 (2021)DO - 10.24843/EJMUNUD.2021.v10.i02.p02, 2021)
Company performance is a condition produced by a company with reference to the company's performance appraisal standards. Performance is used as an evaluation material for management of the quality and level of organizational performance. In managing quality, companies need to implement a quality management system, namely Total Quality Management (TQM). Companies also need to pay attention to the maintenance of a service object in order to keep it functioning properly. This study aims to determine the performance of companies that are affected by TQM and the role of maintenance in strengthening or weakening the influence of TQM on company performance. This study used a saturated sample of 96 crew / staff through interviews and questionnaires with the data analysis techniques used, namely Factor Analysis and Moderated Regression Analysis (MRA). This study results in a maintenance role that can strengthen the influence of TQM on company performance. The results of this study can  guidelines through the implementation of maintenance and quality dimensions. Keywords : TQM, Maintenance, Company Performance.